Demonstration of fast multi‐slice quasi‐steady‐state chemical exchange saturation transfer (QUASS CEST) human brain imaging at 3T. Issue 2 (30th September 2021) - Kim, Hahnsung; Krishnamurthy, Lisa C.; Sun, Phillip Zhe
Abstract : Purpose: To combine multi‐slice chemical exchange saturation transfer (CEST) imaging with quasi‐steady‐state (QUASS) processing and demonstrate the feasibility of fast QUASS CEST MRI at 3T. Methods: Fast multi‐slice echo planar imaging (EPI) CEST imaging was developed with concatenated slice acquisition after single radiofrequency irradiation. The multi‐slice CEST signal evolution was described by the spin‐lock relaxation during saturation duration (Ts ) and longitudinal relaxation during the relaxation delay time (Td ) and post‐label delay (PLD), from which the QUASS CEST was generalized to fast multi‐slice acquisition. In addition, numerical simulations, phantom, and normal human subjects scans were performed to compare the conventional apparent and QUASS CEST measurements with different Ts, Td, and PLD. Results: The numerical simulation showed that the apparent CEST effect strongly depends on Ts, Td, and PLD, while the QUASS CEST algorithm minimizes such dependences. In the L‐carnosine gel phantom, the proposed QUASS CEST effects (2.68 ± 0.12% [mean ± SD]) were higher than the apparent CEST effects (1.85 ± 0.26%, p < 5e‐4). In the human brain imaging, Bland‐Altman analysis bias of the proposed QUASS CEST effects was much smaller than the PLD‐corrected apparent CEST effects (0.03% vs. −0.54%), indicating the proposed fast multi‐slice CEST imaging is robust and accurate. Conclusions: The QUASS processing enables fast multi‐slice CEST imaging with minimal loss in the measurement of the CEST effect.